A promising approach for the recovery of high value-added metals from spent lithium-ion batteries - Hu, Juntao; Zhang, Jialiang; Li, Hongxu; Chen, Yongqiang; Wang, Chengyan (Journal of power sources, 2017)
The aim of the paper is to present a promising approach for recycling high value-added metals from the cathode materials of spent LIBs. The synthesis process of NCM cathode material enlightened us to apply reduction roasting to break LiNixCoyMnzO2 into simple compounds or metals. Accordingly, the effect of several factors such as temperature, carbon dosage and roasting time is assessed on the leaching efficiency of valuable metals. The roasted products are analyzed by XRD and SEM-EDS, and the results show that the cathode material after reduction roasting is primarily transformed into Li2CO3, Ni, Co and MnO. However, the solubility of Li2CO3 is relatively low, so carbonated water leaching is used to treat the roasted products. Then the filtrate is evaporated for the preparation of pure Li2CO3, and residue is leached to recycle other metals with H2SO4. The results indicate that, after roasted at 650 °C for 3 h with 19.9% carbon dosage, 84.7% Li is preferentially recovered via carbonated water leaching, and more than 99% Ni, Co and Mn are recycled via acid leaching without adding reductant. Finally, the products of Li2CO3, NiSO4, CoSO4 and MnSO4 are obtained. The process have great potential for industrial-scale recycling from spent LIBs. [Display omitted] •A simple and efficient process is proposed for recovering spent LIBs.•LiNixCoyMnzO2 was transformed into Li2CO3, Ni, Co and MnO by reduction roasting.•Carbonated water leaching was used to selectively recover Li from roasted products.•Co, Ni and Mn were efficiently leached by H2SO4 solution without adding reductant.•The products of Li2CO3, NiSO4, CoSO4 and MnSO4 were obtained.